Performance evaluation of a mechanical vapor compression desalination system - Bahar, Rubina; Hawlader, Mohammad Nurul Alam; Woei, Liang Song (Elsevier, 2004)
Desalination processes are making rapid technological progresses for the conversion of seawater to fresh water. In this study, experiments have been performed on a mechanical vapor compression desalination system (MVC). The MVC pilot plants has two vertical evaporator condensers and its rated capacity is about 1 m3/d. The performance of the system has been evaluated under variable operating conditions, where the different values of brine recirculation rate and compressor speed were considered. Throughout the experiment, the top brine temperature was kept constant at a value of 103°C. For different concentrations ranging from 20,000 ppm to 33,000 ppm, the influence of increasing brine recirculation rate and compressor speed were observed. It has been found that the performance is better with lower concentration and increased compressor speed. The highest average PR obtained was 2.52.